2005
DOI: 10.1124/jpet.105.090043
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Novel Antifolate Pemetrexed to the Brain

Abstract: Pemetrexed disodium is a novel antifolate that exhibits potent inhibitory effects on multiple enzymes in folate metabolism. Phase II/III clinical trials have shown that pemetrexed is effective against various solid tumors. Like methotrexate, pemetrexed may be useful in treatment of primary and secondary brain tumors. In this study, we examined the central nervous system (CNS) distribution of pemetrexed and the interaction with an organic anion transport inhibitor indomethacin. Male Wistar rats were administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Certain studies have indicated that gefitinib and erlotinib penetrate into the central nervous system and elicit responses in NSCLC patients with brain metastases (13)(14)(15). It was revealed that pemetrexed had a slightly higher brain penetration capability compared to that of methotrexate, by the analysis of arterial blood and frontal cortex microdialysis samples obtained simultaneously (7,8). Bearz et al (16) investigated the therapeutic effect of pemetrexed on reducing brain metastases and revealed that PR (partial remission) was observed in 11 patients (28.2%) and SD (stable disease) was observed in 21 patients (53.8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have indicated that gefitinib and erlotinib penetrate into the central nervous system and elicit responses in NSCLC patients with brain metastases (13)(14)(15). It was revealed that pemetrexed had a slightly higher brain penetration capability compared to that of methotrexate, by the analysis of arterial blood and frontal cortex microdialysis samples obtained simultaneously (7,8). Bearz et al (16) investigated the therapeutic effect of pemetrexed on reducing brain metastases and revealed that PR (partial remission) was observed in 11 patients (28.2%) and SD (stable disease) was observed in 21 patients (53.8%).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are involved in the synthesis of nucleotides, and ultimately pemetrexed is capable of interfering with RNA and DNA synthesis procedures (6). It was revealed that pemetrexed had a slightly higher brain penetration capability than methotrexate by the analysis of arterial blood and frontal cortex microdialysis samples obtained simultaneously (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Several expressions have been used to describe drug delivery to the brain in the literature: permeation (Tamai and Tsuji 2000;Abbott et al 2008), brain penetration (Schinkel et al 1996), extent of brain penetration (Liu et al 2008), CNS penetration (Summerfield et al 2006), BBB penetration (Gunn et al 2012), brain delivery (Pardridge et al 1992), and CNS distribution (Dai et al 2005;Kalvass et al 2007a). The expressions used for the total brain-to-total plasma concentration ratio also vary: [brain]/[plasma] (Kalvass and Maurer 2002), K p (a classical expression in pharmacokinetics for the partition coefficient between tissue and plasma (Rowland and Tozer 2011)), K p,brain (Gupta et al 2006), and B/P (Maurer et al 2005).…”
Section: Historical Aspects On Studying Brain Drug Deliverymentioning
confidence: 98%
“…It has been reported to have potent antitumor activity against a variety of tumors including CNS malignancies (Kuo and Recht, 2006). However, similar to MTX, distribution of PMX across the BBB is also very limited (Dai et al, 2005). The mechanisms behind the poor brain penetration of PMX and MTX are not well understood; one plausible explanation has been the involvement of efflux transport systems at the BBB.…”
Section: Introductionmentioning
confidence: 95%
“…Most of the systemic toxicities can be attributed to the greater tissues exposure after treatment with MTX at high doses, a need arising from the inability of MTX to penetrate the BBB. Preclinical studies have shown that brain distribution of MTX is severely restricted: only 5% of the free drug in plasma crosses the BBB to reach the brain (Devineni et al, 1996;Dai et al, 2005). In humans, Blakeley et al (2009) also reported poor cerebral penetration of MTX (3.2 to 9.4%) using the microdialysis technique in patients who have recurrent high-grade gliomas.…”
Section: Introductionmentioning
confidence: 99%